Aulas hospitalarias como estrategia de inclusión educativa para niños de 4 a 12 años en condición de hospitalización en los hospitales del cantón Loja, periodo 2022- 2023. - Rojas Espinoza, Pablo Andrés (2024)
The present study carried out during the period 2022-2023 focuses on Hospital Classrooms as an educational inclusion strategy for children from 4 to 12 years old in hospitalization in hospitals in the Loja canton; The research had a mixed approach, the participants were the coordinator of the District Inclusion Support Unit "UDAI", teachers, parents and students; The instruments applied were: surveys, interviews, knowledge assessment, documentary review and observation; Three objectives were proposed, the first focused on knowing the means used in the implementation of the Hospital Classrooms Program, identifying that the hospitals of the Loja canton implement the program through an inter-institutional cooperation agreement between the Ministry of Education and the Ministry of Health through the National Model of Hospital and Home Educational Management and Care, focused on five key approaches to improve the quality of life of hospitalized children; A second objective focused on the identification of problems presented during the implementation of the Hospital Classrooms, having recognized inconveniences related to the adaptation of physical spaces and the limited provision of technological educational materials by the Ministry of Education; The third objective was to determine if the children managed to overcome the academic delays, verifying that the children assigned to the Hospital Classrooms Program managed to overcome the academic delays thanks to the comprehensive approach; which included individual curricular adaptations and constant feedback from teachers. This is backed up by academic records, which not only indicated that students passed the school year, but also managed to overcome the additional challenges stemming from their health situation. The study highlights the importance of the Hospital Classrooms Program as an effective educational inclusion strategy for hospitalized children in Loja.